A new genus and new species of alpheid shrimp from a marine cave in the Ryukyu Islands, Japan, with additional record of Salmoneus antricola Komai, Yamada & Yunokawa, 2015 (Crustacea: Decapoda: Caridea) - Komai, Tomoyuki; Fujita, Yoshihisa (Zootaxa, 2018)
Two species of alpheid shrimp collected from a marine cave off Ie Island, Okinawa Islands, Ryukyu Islands, Japan, are reported. Caligoneus cavernicola n. gen., n. sp., is described on the basis of six specimens, including two ovigerous individuals. The new monotypic genus shares a number of features with Salmoneus Holthuis, 1955 and Triacanthoneus Anker, 2010; however, the dorsally elevated rostrum and the symmetrical pereopods 1 (= chelipeds) of “minor form” distinguish Caligoneus n. gen. from the latter two genera. Other potentially diagnostic characters between the new genus and the latter two genera are also discussed. The new taxon is clearly adapted to stygobiotic environments, with its reduced cornea and very slender elongate pereopods. In addition, two complete specimens of Salmoneus antricola Komai, Yamada & Yunokawa, 2015, collected in the same cave, supplement the original description of the species, which was based on a unique holotype with a damaged telson.